Compartment syndrome due to Capnocytophaga canimorsus infection: a case report. Issue 1 (1st January 2020) - Igeta, Ryuhei; Hsu, Hsiang‐Chin; Suzuki, Michio; Lefor, Alan T.; Tsukuda, Jumpei; Endo, Takuro; Tanii, Rimi; Taira, Yasuhiko; Fujitani, Shigeki
Abstract : Background: Purpura fulminans secondary to Capnocytophaga canimorsus ( C. canimorsus ) infection without a wound is rare and often misdiagnosed initially. We report a patient who died due to C. canimorsus bacteremia with purpura fulminans and acute compartment syndrome of all extremities. Care Presentation: A 38‐year‐old Japanese man with a history of alcoholism presented with a 2‐day history of gastroenteritis. The chief complaints were abdominal pain and diarrhea, and he had abdominal tenderness. Laboratory findings showed multiple organ failure. On day 2, pain in the lower extremities associated with motor and sensory dysfunction developed. On day 3, purpura on the whole body spread to all extremities. All four extremities became rigid, and acute compartment syndrome developed. The patient died due to uncontrolled hyperkalemia and lactic acidosis. Conclusions: Capnocytophaga canimorsus transmission can occur through licking or even close contact with animals when a risk factor of C. canimorsus infection, such as alcoholism, is present.